Uji Konstruk dan Pengukuran Resiliensi Berdasarkan Jenis Kelamin Menggunakan Analisis Pemodelan Rasch - Maria Oktasari; Herul Wahyudin (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2021)
This study aims to (1) perform theoretical construct testing on students’ resilience inventory and (2) measuring student’s resilience based on gender. This study used a survey method with a sample of 40 high school students in Bandung. Data analysis used the RASCH model. These research findings show (1) inventory resilience has been fit with the theoretic model, and (2) female student has a tendency to a higher resilience rather than the male student. Furthermore, the measurement of student’s resilience by using this inventory can only produce high measurement information for students who have the intermediate ability. So, the researcher needs to consider eliminating item No. 18 in this inventory due to the biased towards the female gender.